Features of the Clinical Course of Infective Endocarditis in Children - Oleksandr H. Senko (Ukrainian Journal of Cardiovascular Surgery, 2025)
Infective endocarditis (IE) in children is less common than in adults but is associated with a significantly higher mortality rate. At the same time, diagnosis and treatment in young patients are complicated by a higher prevalence of congenital heart defects (CHD). We studied the spectrum of microorganisms and clinical manifestations in children.Aim. To study the features of the clinical course of infective endocarditis in children.Materials and methods. A retrospective study of surgical treatment cases of IE in children treated from 1994 to 2023 at the Amosov National Institute of Surgery and Epidemiology was conducted. Clinical manifestations, treatment, complications, outcomes of IE, and the spectrum of etiotropic pathogens were analyzed.Results. Seventy-one patients underwent surgery from 1994 to 2023, all of whom had intraoperative confirmation of IE and were minors at the time of hospitalization. Among the 71 children, 12 were infants (16.9 %). The distribution according to congenital heart disease was as follows: cyanotic CHD – 10 (14.1 %), non-cyanotic CHD – 37 (52.1 %), without congenital pathology – 24 (33.8 %). The overall hospital mortality rate was 9.8 % (7 out of 71 patients). The distribution of identified pathogens was as follows: in 55 (77.5 %) patients, the pathogen could not be identified; in 13 (18.3 %) cases – gram-positive pathogens; in 1 (1.4 %) case – a gram-negative microorganism; and in 2 (2.8 %) cases, fungi were detected. Nosocomial infection was diagnosed in 16 (22.5 %) children. Cardiac surgery in history was performed in 13 (18.3 %) children.Conclusions. The treatment of children with IE is complicated by the low rate of pathogen detection among patients with this pathology. The predominant pathogens among those detected are gram-positive microorganisms. Prevention of IE in children at increased risk (presence of CHD, previous heart surgery, intracardiac synthetic materials, and concomitant sources of infection) is essential.